International Posture Of Malaysian Learners In Arabic Programme - Bakar, Kaseh Abu; Asbulah, Lily Hanefarezan; Mohamad Soad, Nor Fatini Aqilah; Ahmad, Mohd Farhan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Language learners with a solid international posture are generally more willing to communicate in the foreign language they learn. However, studies on global posture could have been conducted better, especially for Arabic language learners. Therefore, this study aims to examine the level of readiness of students of Arabic studies programs in terms of international posture. This study uses a quantitative design by distributing online questionnaire instruments to 180 final-year students of the bachelor’s degree from three public universities in Malaysia, namely Universiti Kebangsaan Malaysia (UKM), Universiti Sains Islam Malaysia (USIM), and International Islamic University (UIA). Data were analyzed using SPSS version 25. The results showed that students in tertiary Arabic Studies programs in Malaysia report that international posture is in the moderate range but relatively lower. Students need to capitalize on all these aspects, which will directly and indirectly contribute to better achievement in learning Arabic.